A Shaving Proteomic Approach to Unveil Surface Proteins Modulation of Multi-Drug Resistant Pseudomonas aeruginosa Strains Isolated From Cystic Fibrosis Patients - Montemari, Anna Lisa; Marzano, Valeria; Essa, Nour; Levi Mortera, Stefano; Rossitto, Martina; Gardini, Simone; Selan, Laura; Vrenna, Gianluca; Onetti Muda, Andrea; Putignani, Lorenza; Fiscarelli, Ersilia Vita (Frontiers in Medicine, 2022)
Cystic fibrosis (CF) is the most common rare disease caused by a mutation of the CF transmembrane conductance regulator gene encoding a channel protein of the apical membrane of epithelial cells leading to an alteration of Na+ and K+ transport. Consequently, dense and sticky mucus can be accumulated, hence promoting recurrent airway infections. The most detected microorganism in CF patients, especially in adolescents and adults, is Pseudomonas aeruginosa; this ubiquitous Gram-negative bacterium is the causative agent of most lung diseases and is responsible of chronic colonization, usually correlated to respiratory impairment and to an increase in morbidity and mortality. Subsequent pulmonary exacerbations require increasing antibiotic therapies triggering microbial multi-drug resistance. Despite eradication attempts at the first infection, P. aeruginosa is featured with high plasticity and is able to pursuit adaptation mechanisms that allow it to survive in hostile environments such as the CF lungs. Its adaptive machinery includes modulation of surface molecules such as efflux pumps, flagellum, pili and other virulence factors. In the present study we compared, by a shaving proteomics approach, surface protein expression of multi- and pan-drug resistant strains of P. aeruginosa isolated from the airways of CF patients with long-term chronic colonization to wild-type antibiotic-sensitive strains isolated from patients with recent infection. These findings may contribute to the comprehensive landscape description of P. aeruginosa surface proteins related to antibiotics resistance and virulence profile. The characterisation of modulated proteins will be the key to decode the functional activity of P. aeruginosa infection and antibiotic resistance in CF, thus having a valuable impact in unveiling new virulence markers and therapeutic targets.